Teacher Training: Tech Savvy Educator Community Service For Teachers In Learning Center, PPMT Parung - Stella Stefany; Rijanto Purbojo (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Getting into Indonesia roadmap program "Making Indonesia 4.0", most of the sector industries have to divert their business into digital. Education as a stakeholder that support these main industries highlighted to put concern about digitizing their learning program. As a part of mission service, GKY Puri Indah nurturing scholar-teacher chain in a continuous program. They built several learning centers to facilitate students in improving their learning skills after school as a part of nurturing future leaders, especially for churches. Before assigned to churches, these graduates have to teach in the learning center for two years. The problem is how can these theological graduates play their role as a teacher. Teacher training systemic program that will be held continuously to educate these teachers. At the first session, conducted in two parts. First part highlighted topic about motivation, teaching, and learning, the second one, highlighted effective communication mediated by technology and approaches in using technology for managing the classroom. The method used in this community service is lecturing, discussion, and presentation as evaluation, divided into 4 phases: preparation, delivery, assessment, and evaluation. Result of this program is some motivated participants are needed to be enriched by consistent training at least twice in a year to improve their teaching skills and technology use in education.